Comparative study of the adsorption of tetracycline on clay minerals with various nanostructures: allophane, halloysite, and montmorillonite; Clays and Clay Minerals; Vol. 72 - Ma Qiyi; Zhao Ning; Wang Shun; Zhang Baifa; Li Mengyuan; Liu Dong; Zhou Xiang; Rudmin M. A. Maksim Andreevich; Mulaba-Bafubiandi A. F. Antoine; Yuan Peng (2024, 2024)
Title screen